Modular version of Goebel-Kirk theorem - Kozlowski, Wojciech M. (Topological Methods in Nonlinear Analysis, 2024)
In this paper we prove a fixed point theorem for asymptotically nonexpansive mappings acting in modular spaces. This result generalises the 1972 fixed point theorem by K. Goebel and W.A. Kirk. In the process, we extend several other results (including the Milman-Pettis theorem) from the class of Banach spaces to the larger class of regular modular spaces.